Forging Movement: The Strigil in Athenian Vase Painting Iconography. - Young, Yael (Scripta Classica Israelica, 2025)
The transition from the black to the red-figure technique during the last quarter of the sixth century BCE is bound up with a radical change in the depiction of the human body. Suddenly we begin to see foreshortening, three quarter views, a variety of poses and postures, and a more vivid and realistic image of the body. The purpose of this article is to suggest that objects played a crucial role in this radical change, for it was supported, augmented, and sometimes even generated by the representation of humans engaged with objects. To bolster this claim and bring a leading example of an object playing this crucial role, the article focuses on the case of the strigil, an instrument with a sickle-shaped curved blunt blade, used for scraping off oil, sweat, and dirt after athletic exercise. From the time of the introduction of the strigil into Athenian red-figure vases in the late sixth century BCE, most probably by the painter Euthymides, the number of such depictions rapidly increased. It is apparent that, from the very beginning, the vase painters were interested in exploring the relationship between the strigil and the naked male body, as evidenced in the creation and use of the apoxyomenos, an iconographic motif in which the strigil interacts with the entire body and guides its movements. This iconography gave the vase painters the chance, and even the excuse, to represent postures and viewpoints hitherto unknown in vase painting. In these images, the strigil generates the movement and disciplines the body: body and strigil are entities existing in a reciprocal relationship. The motif of the apoxyomenos encapsulates the notion that the radical change in the depiction of the human body is entangled with the depiction of objects surrounding it. This notion becomes even more conspicuous when compared to two related iconographical motifs, namely oil rubbing and oil pouring: in these, objects play a minimal role, if any, and they remained marginal in athletic iconography.